GENCODE 2021. Issue Volume 49:Issue D1(2021) (3rd December 2020) - Frankish, Adam; Diekhans, Mark; Jungreis, Irwin; Lagarde, Julien; Loveland, Jane E; Mudge, Jonathan M; Sisu, Cristina; Wright, James C; Armstrong, Joel; Barnes, If; Berry, Andrew; Bignell, Alexandra; et al.
Abstract: The GENCODE project annotates human and mouse genes and transcripts supported by experimental data with high accuracy, providing a foundational resource that supports genome biology and clinical genomics. GENCODE annotation processes make use of primary data and bioinformatic tools and analysis generated both within the consortium and externally to support the creation of transcript structures and the determination of their function. Here, we present improvements to our annotation infrastructure, bioinformatics tools, and analysis, and the advances they support in the annotation of the human and mouse genomes including: the completion of first pass manual annotation for the mouse reference genome; targeted improvements to the annotation of genes associated with SARS-CoV-2 infection; collaborative projects to achieve convergence across reference annotation databases for the annotation of human and mouse protein-coding genes; and the first GENCODE manually supervised automated annotation of lncRNAs. Our annotation is accessible via Ensembl, the UCSC Genome Browser and https://www.gencodegenes.org .